Investigation of catalysts with Dynamic Nuclear Polarization solid-state NMR - Mais, Marco (2020)
Solid-state nuclear magnetic resonance (NMR) is a powerful method for studying the molecular structure and dynamics of a broad range of systems from heterogeneous materials to biological molecules through the interaction of the nuclear spins with a radiofrequency field. Information about the chemical environment of the atoms can be extracted from nuclear spin interactions like chemical shift and quadrupolar coupling. The majority of elements possesses at least one isotope with spin greater than zero, so they can be analyzed with NMR. However, NMR suffers from low sensitivity, because of the small nuclear spin polarizations involved even with high magnetic fields, and so long acquisition times or large sample volumes are required. The problem of sensitivity becomes overwhelming for dilute species, so that measurements of adsorbates on surfaces, molecules at interfaces or isotopes with low natural abundance are often impossible. The study of solid catalysts by NMR is particularly challenging because of the low concentration of active sites and the small fraction of the entire material present at the surface. Weak NMR signals can be enhanced by dynamic nuclear polarization (DNP), which involves transfer of electron spin polarization from implanted radicals in the sample to nearby nuclei. This process requires the saturation of the electronic Zeeman transitions and until recently has been limited to low magnetic fields because of the lack of high-frequency, high power microwave sources. However, recent developments in the design of gyrotrons have made high-field DNP NMR spectrometers possible. The substantial enhancements (up to 300-fold) obtained with DNP make NMR studies of dilute species feasible for the first time and have already prompted new NMR applications to surfaces and materials which are porous or particulate on the micro- to nanoscale. In the future DNP-enhanced experiments will dramatically transform solid-state NMR studies of a broad range of technologically useful materials with applications in gas storage and sequestration, therapeutic delivery, heterogeneous catalysis, and tissue engineering. The aim of this thesis is to apply DNP-enhanced solid-state NMR to structural and mechanistic studies of catalysts of a wide range of materials from transition metals supported on oxide surfaces to polymeric fibres and complex functionalized materials for catalysis.